Isolation and characterization of soil actinobacteria as cellulolytic enzyme producer from Aceh Besar, Indonesia - Lenni Fitri; MOHAMMAD ADZANNIE BESSANIA; NADIA SEPTI; SUHARTONO SUHARTONO (Society for Indonesian Biodiversity, 2021)
Abstract. Fitri L, Bessania MA, Septi N, Suhartono S. 2021. Isolation and characterization of soil actinobacteria as cellulolytic enzyme producer from Aceh Besar, Indonesia. Biodiversitas 22: 5169-5180. Cellulolytic actinobacteria are cellulase-producing bacteria capable of degrading cellulose. This study aimed to isolate, characterize, evaluate the cellulolytic ability, and to determine physiological characterization of soil cellulolytic actinobacteria isolated from the Ujung Pancu area, Aceh Besar. Isolation of actinobacteria from soil samples was performed using serial dilution method on Yeast Malt Agar (YMA) medium. Morphological characterization was carried out by growing isolates on YMA, Oatmeal Agar (OA), and Yeast Starch Agar (YSA) media. Cellulolytic ability was determined by calculating the cellulolytic index (IS) on 1% carboxymethyl cellulose (CMC) medium after adding 0.1% congo red solution. Physiological characterization of cellulolytic actinobacteria tested in this study was salinity, pH, and carbon source in liquid Yeast Malt (liquid YM), and the growth was measured at a wavelength of 581nm. The results showed that a total of nine isolates of actinobacteria were isolated, which belonged to the genus Streptomyces. Cellulolytic test results showed that eight isolates had the ability to degrade cellulose. Isolates AUP-04, AUP-03, and AUP-01 had the highest cellulolytic index value. Physiological characterization results revealed that three isolates had different tolerances for salinity levels, pH, and types of carbon sources. AUP-03 isolate grew well at 10% salinity with an OD value of 0.88, isolate AUP-01 grew at 5% salinity with an OD value of 0.49, whereas isolate AUP-04 grew well on media that did not contain salinity. All three isolates grew well at pH 6 with OD values of 0.93, 1.12, and 1.27. AUP-03 and AUP-01 isolates grew well on media containing dextrose as carbon source with OD values of 0.154 and 0.17, respectively, while isolate AUP-04 grew well on glucose-containing media with an OD value of 0.22.